The Applicability of Constructivism Theory in the Learning Process of Islamic Religious Education for Students - Nurhasanah, Enung (Jurnal Pendidikan Indonesia, 2025)
The problem in this study lies in the lack of application of learning approaches that can actively and independently build students' knowledge, especially in Islamic Religious Education courses. This suggests the need for further research on how the application of constructivist theory can enhance the effectiveness of the learning process. This study aims to analyze the application of constructivism theory in the learning process of Islamic Religious Education for students. This research method uses qualitative description. The data collection methods used are observation, interviews, and documentation. Data analysis in this study consists of three analysis flows: data reduction, data display, and verification. This study demonstrates that the application of constructivist theory in Islamic Religious Education (PAI) learning has been successful in increasing students' active involvement. It is concluded that the application of constructivist theory in Islamic Religious Education learning can increase active participation and understanding among students through a student-centred learning process. This approach encourages students to build knowledge independently through discussion, reflection, and direct involvement in learning activities. This study highlights the importance of adopting a more student-centred approach and providing lecturer training in applying constructivist methods to enhance the quality of learning in higher education.